Etiology and management of perforation peritonitis: perspective from developing world - Bali, Rajandeep Singh; Sharma, Ashok Kumar; Soni, Rajesh Kumar (International Surgery Journal, 2017)
Background: Gastrointestinal perforation peritonitis is one of the commonest surgical emergencies encountered by surgeons all over the world. Methods: Present study was a retrospective study conducted at Lok-Nayak Hospital by analyzing the case records of 246 patients of perforation peritonitis presenting to the Emergency Department from January 2012 to December 2015. Results: A total of 246 patients were analyzed retrospectively. Mean age of present study group was 38.6 years, with male to female ratio of 2:1. The commonest etiology was gastro-duodenal ulcers followed by (in order of decreasing frequency) appendicitis, typhoid, trauma, tuberculosis, malignancy, bowel strangulation, amoebiasis, diverticulitis and unknown etiology. Mortality was 20 (8.13%) cases in the present study group. Conclusions: The spectrum of etiology of perforation peritonitis in the developing world differs markedly from that in the developed world. Early and aggressive fluid and electrolyte correction followed by prompt surgical intervention to address the cause under the cover of broad spectrum antibiotics are the cornerstones in achieving a favourable and good outcome.